2018
DOI: 10.1016/j.chom.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Infection-Induced Peroxisome Biogenesis Is a Metabolic Strategy for Herpesvirus Replication

Abstract: Summary Viral proteins have evolved to target cellular organelles and usurp their functions for virus replication. Despite the knowledge of these critical functions for several organelles, little is known about peroxisomes during infection. Peroxisomes are primarily metabolic organelles with important functions in lipid metabolism. Here, we discovered that the enveloped viruses human cytomegalovirus (HCMV) and herpes simplex virus (HSV-1) induce the biogenesis of and unique morphological changes to peroxisomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 53 publications
1
75
2
Order By: Relevance
“…We found that our observations matched most descriptions of host cell rearrangements like redistribution and bundling of microtubules [27,28] (13-16 hpi, MOI 3-5), loss of centrosome/MTOC [28] (13 hpi, MOI 5), migration of mitochondria towards perinuclear region [29] ( 6 hpi, MOI 5), and fragmentation of the Golgi apparatus [11,27] (8-12 hpi, MOI 3-10) very well. An exception were peroxisomes, where we did not observe previously described morphological changes, possibly because they were previously identified at later times post infection (16 hpi, MOI 5; Jean Beltran et al [30]).…”
Section: Discussioncontrasting
confidence: 50%
“…We found that our observations matched most descriptions of host cell rearrangements like redistribution and bundling of microtubules [27,28] (13-16 hpi, MOI 3-5), loss of centrosome/MTOC [28] (13 hpi, MOI 5), migration of mitochondria towards perinuclear region [29] ( 6 hpi, MOI 5), and fragmentation of the Golgi apparatus [11,27] (8-12 hpi, MOI 3-10) very well. An exception were peroxisomes, where we did not observe previously described morphological changes, possibly because they were previously identified at later times post infection (16 hpi, MOI 5; Jean Beltran et al [30]).…”
Section: Discussioncontrasting
confidence: 50%
“…For example, the number of peroxisomes increases when rodents are administered fibrate derivatives but decreases rapidly upon withdrawal of the drugs ( Fahimi et al, 1982 ; Yokota, 1986 ; Yokota, 1993 ). Enveloped virus infection induces significant peroxisome biogenesis, promoting phospholipid plasmalogen synthesis for virus production ( Jean Beltran et al, 2018 ). Peroxisomes also display heterogeneity in the same cell.…”
Section: Discussionmentioning
confidence: 99%
“…RAW files containing MS/MS spectra collected in PRM mode were imported into Skyline to extract product ion chromatograms (XICs) and calculate peak areas. A human and herpesvirus peptide spectral library was generated using Skyline (v4.0) from DDA MS analyses of Murray et al 83 and Jean Beltran et al 94 . The list of peptides was filtered based on ion intensity and peak area reproducibility across replicates.…”
Section: Lc-ms/ms Analysis For Targeted Ms Using Prmmentioning
confidence: 99%